Interdependence between Inventory Management and Employees’ Satisfaction - Tomašić, Dubravko; Peraković, Dragan; Jurčević, Marinko (Promet - Traffic&Transportation, 2013)
The study determines the correlation between the application of advanced models and methods of inventory optimisation in the supply chain in relation to the satisfaction of employees who are responsible for managing the inventory optimisation processes. The previous studies confirm that the optimisation of inventory management in the supply chain insures competitive advantages on the market. There is space for further research of impact of the achieved inventory optimisation in the supply chain on the change of the employees’ satisfaction. The paper establishes the interrelation of the interdependence of the achieved inventory optimisations on the satisfaction of the employees and the related synergy effects of acquiring added value of the companies on the market oriented to the satisfaction of the buyers and service users. The research has defined new knowledge in interdependence of inventory management optimisation on the change of indicators of employees’ satisfaction. Based on the performed research an assumption has been created for the design of an application package (so-called XaaS-based services) for the management of interaction processes of inventory optimization in the supply chain, satisfaction of service users and employees.